Recent insights into metallic nanoparticles in shelf-life extension of agrifoods: Properties, green synthesis, and major applications - Kumar, Ankit; Kumar, Abhishek; Vats, Chaman; Sangwan, Pooja; Kumar, Vikash; Abhineet,; Chauhan, Prashant; Chauhan, Ravinder S.; Chaudhary, Kautilya (Frontiers in Sustainable Food Systems, 2022)
Nanotechnology emerged as a revolutionary technology in various fields of applied sciences, such as biomedical engineering and food technology. The pivotal roles of nanocompounds have been explored in various fields, such as food protection, preservation, and enhancement of shelf life. In this sequence, metallic nanoparticles (MNPs) are proven to be useful in developing products with antimicrobial activity and subsequently improve the shelf life of agrifoods. The major application of MNPs has been observed in the packaging industry due to the combining ability of biopolymers with MNPs. In recent years, various metal nanoparticles have been explored to formulate various active food packaging materials. However, the method of production and the need for risk evaluation are still a topic of discussion among researchers around the world. In general, MNPs are synthesized by various chemical and physical means, which may pose variable health risks. To overcome such issues, the green synthesis of MNPs using microbial and plant extracts has been proposed by various researchers. In this review, we aimed at exploring the green synthesis of MNPs, their properties and characterization, various ways of utilizing MNPs to extend their shelf life, and, most importantly, the risk associated with these along with their quality and safety considerations.